Survival Outcomes Are Not Affected When Liver Transplant Surgery Is Done at Night, During Weekends, or Summer Months. Issue 5 (May 2019) - Thuluvath, Paul J.; Amjad, Waseem; Savva, Yulia; Thuluvath, Avesh J.; LaMattina, John
Abstract : Background: It has been suggested that hospitalized patients may get suboptimal care in nights or on weekends or summer holidays due to sleep deprivation, physician fatigue, or reduced medical staffing. Our objective was to determine whether there were differences in outcomes when surgery was performed in the night (10 PM–6 AM), on weekends (Saturday or Sunday), or during summer months (June–August). Methods: We used United Network for Organ Sharing (UNOS) data sets of adults transplanted between February 27, 2002, and September 30, 2016. We estimated the start time of liver transplant surgery by utilizing the cross-clamp time and cold ischemia time (cross-clamp time + cold ischemia time – 2 h). The survival outcomes were estimated by Kaplan-Meier survival analysis. Patients with hepatocellular carcinoma (HCC) were analyzed separately. The independent effect of time of transplant on outcomes was analyzed after adjusting for common confounders, including Model for End-stage Liver Diseases scores and transplant center volume. Results: During the study period, 4 434 (9.6%) were done in the night, 12 147 (26.4%) over weekends, and 11 976 (26%) during summer months. The graft and patient survival and complications were not influenced by the time of transplant for both HCC and non-HCC population. Cox regression analysis after adjusting for risk factors, including Model for End-stage Liver Diseases, donor risk index, and liver center volume, confirmed that there were no significant differences in outcomes. Conclusions: Our study showed that the time of transplant surgery whether done during nights, weekends, or summer months had no effect on graft or patient survival irrespective of center volume, patient, or donor risk factors. Abstract : Supplemental Digital Content is available in the text.